Nuclear Superfluidity Pairing in Finite Systems - Brink, David M. (Cambridge University Press, 2005)
Nuclear Superfluidity is a monograph devoted exclusively to pair correlations in nuclei. It begins by exploring pair correlations in a variety of systems including superconductivity in metals at low temperatures and superfluidity in liquid 3He and in neutron stars. The book goes on to introduce basic theoretical methods, symmetry breaking and symmetry restoration in finite many-body systems. The last few chapters are devoted to introducing results on the role of induced interactions in the structure of both normal and exotic nuclei. The most important of these is the renormalization of the pairing interaction due to the coupling of pairs of nucleons to low energy nuclear collective excitations. This book will be essential reading for researchers and students in experimental and theoretical nuclear physics, and related research fields such as metal clusters, fullerenes and quantum dots.